Muhammad Iqbal's Thoughts and its Relevance to Sustainable Development (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Muhammad Iqbal as a Muslim philosopher also a humanitarian activist who voices the rise of Muslim people to achieve equality and justice that always carries the theme of nature in his works. He had deep thoughts in many scientific fields,much research has been done on them, but it rarely mentions his development ideas. In fact, environmental damage and steep economic inequality that are inconsistant with the doctrine of human as universe caliph in Islam, are the impact of technology driven by a capitalistic paradigm that ignores the sustainability of all resources in the world. For that reason, this article is structured through library research as an effort to dissect Muhammad Iqbal's thoughts in the sustainable development.The results are; first, humans are free creatures who can only submit to God, not others. Second, the universe was created by God for the benefit of humans. Both have inseparable existential relationships to maintain sustainability. Be ing responsible humans to understand, manage and utilize it. The relationship between humans and nature is as close as the relationship between humans and God, growth in sustainable creativity.